2023
DOI: 10.1055/a-2021-0596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Thyroid Stimulating Immunoglobulin and TSH-Receptor Antibodies in the Management of Graves’ Orbitopathy

Abstract: Introduction TSH-receptor antibodies (TRAb) targeting the TSH receptor (TSH-R) induce hyperthyroidism in Graves´ disease (GD). Graves´ orbitopathy (GO) is influenced by a stimulation of the TSH-R in the orbita. GO has been, among other factors, linked to high TRAb levels. Thyroid stimulating immunoglobulins (TSI) is a relatively new method for assessing TSH-receptor antibodies. The aim of this study was to investigate the role of TSI in management of GO. Materials and methods Patients with newly diagnosed GD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Recent studies have also demonstrated the utility of a few newer methods for the measurement of TSHrAb such as one-step third-generation radioimmunoassay and dot-blot method are useful, albeit with modestly lower diagnostic accuracy of the latter method [24,25]. Thyroid stimulating antibody (TSI), the best method for assessment of autoimmunity in Graves' disease, may have better diagnostic performance in diagnosing Graves' disease, and offer a better prediction of thyroidassociated orbitopathy and response to antithyroid therapy [26][27][28]; however, the reports are variable and advantages in clinical practice are minimal [29]. Moreover, this assay is not currently available in India.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also demonstrated the utility of a few newer methods for the measurement of TSHrAb such as one-step third-generation radioimmunoassay and dot-blot method are useful, albeit with modestly lower diagnostic accuracy of the latter method [24,25]. Thyroid stimulating antibody (TSI), the best method for assessment of autoimmunity in Graves' disease, may have better diagnostic performance in diagnosing Graves' disease, and offer a better prediction of thyroidassociated orbitopathy and response to antithyroid therapy [26][27][28]; however, the reports are variable and advantages in clinical practice are minimal [29]. Moreover, this assay is not currently available in India.…”
Section: Discussionmentioning
confidence: 99%
“…34 On the contrary, Khamisi et al did not show additional benefit of using TSI compared to the conventional TRAb assay in a Japanese study. 35 A systematic review revealed that the discrepancies in the relationship between TBII and TSI could be due to ethnic differences. The relationship between TED and TBII seems to be stronger in Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…Research herein has primarily focused on the use of different assays as a biomarker for disease activity and severity, showing that TSI bioassays, outperform TBII assays (4,5,7,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). So far, only a limited number of studies investigated the applicability of the bridge-based TSI binding assay as a biomarker for disease activity and severity in GO, with conflicting results (26)(27)(28)(29)(30). Although identifying patients with active disease is important, it may be even more relevant to identify patients who will not respond to intravenous methylprednisolone (IVMP).…”
Section: Introductionmentioning
confidence: 99%